2016
DOI: 10.3382/ps/pew076
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the addition of β-mannanase on the performance, metabolizable energy, amino acid digestibility coefficients, and immune functions of broilers fed different nutritional levels

Abstract: Three experiments were conducted to evaluate the effect of β-mannanase (BM) supplementation on the performance, metabolizable energy, amino acid digestibility, and immune function of broilers. A total of 1,600 broilers were randomly distributed in a 4 × 2 factorial arrangement (4 nutritional levels × 0 or 500 g/ton BM), with 10 replicates and 20 broilers per pen. The same design was used in the energy and digestibility experiments with 8 and 6 replicates, respectively, and 6 broilers per pen. The nutritional l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 22 publications
4
19
0
1
Order By: Relevance
“…Decreasing thymus weight percent by βmannanase supplementation agree with Zou, et al (2006). Moreover the relative decrease in thymus weight percent by βmannanase supplementation was about 27%, this result was in agreement with Ferreira et al (2016).…”
Section: Organs Weight Percent (% Live Body Weight)supporting
confidence: 88%
“…Decreasing thymus weight percent by βmannanase supplementation agree with Zou, et al (2006). Moreover the relative decrease in thymus weight percent by βmannanase supplementation was about 27%, this result was in agreement with Ferreira et al (2016).…”
Section: Organs Weight Percent (% Live Body Weight)supporting
confidence: 88%
“…These results may indicate that dietary β-mannanase has little effects on true energy metabolizability in ingredients and diets fed to broiler chickens. However, previous experiments reported that dietary β-mannanase increased apparent metabolizability of nutrients [ 9 , 11 ] and energy [ 20 ] in diets fed to broiler chickens. The reason for this discrepancy is not clear, but it may be related to the effect of dietary β-mannanase on endogenous energy losses because we measured true metabolizable energy but previous experiments measured apparent metabolizable energy as affected by dietary β-mannanase.…”
Section: Resultsmentioning
confidence: 99%
“…Feeding of prebiotics (beta mannans) was found to increase immune status and enhance the macrophage activity along with T-helper cell activities (Shohani et al, 2013) and increased most of the relative immune organ weights and significantly increased the concentration of serum IgM. Moreover, βmannanase (Hemicell) supplementation can attenuate the immune response of broilers caused by the reduced production of immunoglobulins (IgA) (Li et al, 2010 andFerreira et al, 2016) and leukocytes (Mehri et al, 2010) because of the mannans present in the feed stimulate the immune system. Li et al (2010) and Ferreira et al (2016) found that supplementing diets with β-mannanase reduced the weights of immunity related organs such as the thymus and bursa of Fabricius.…”
Section: Interleukinsmentioning
confidence: 99%
“…Moreover, βmannanase (Hemicell) supplementation can attenuate the immune response of broilers caused by the reduced production of immunoglobulins (IgA) (Li et al, 2010 andFerreira et al, 2016) and leukocytes (Mehri et al, 2010) because of the mannans present in the feed stimulate the immune system. Li et al (2010) and Ferreira et al (2016) found that supplementing diets with β-mannanase reduced the weights of immunity related organs such as the thymus and bursa of Fabricius. It has been reported that prebiotics as mannan oligosaccharides from yeast cell wall works by providing specific binding sites to enteric pathogens, thus reduces their chances to attach to the intestinal tract and these oligosaccharides being not digested by the endogenous enzymes of the bird pass through the gut with the pathogens attached thus producing a cleaning up effect (Zopf and Roth, 1996).…”
Section: Interleukinsmentioning
confidence: 99%
See 1 more Smart Citation